Internal Democracy and The Politics of Defection in Nigeria’s Fourth Republic - Nwoko, Kenneth; Nweke, Kenneth (University of Nigeria Journal of Political Economy, 2023)
This study undertook a comprehensive appraisal of the nature of internal democracy in Nigeria, vis-a-vis its impact on the circumstances that promote the sustained rise in incidences of inter-party cross-carpeting by politicians, particularly in this fourth republic era. The background to this study demonstrated the widely-acknowledged role political parties play in entrenching and advancing the virtues of democracy in a society’s political system. It however, decried the prevalence of tendencies relating to members-leadership gladiatorial relationship, leadership impunity and the flagrant derogation of the relevance of party ideology in Nigeria’s internal democratic system. Thus, aggravating the gale of inter-party defections. The study relied on secondary sources like textbooks, journals, newspapers and internet materials for data generation. The institutional theory on which the study was anchored, emphasized the indispensable importance of values, norms and principles in determining the fortunes or otherwise, of institutions like the political party. The study further revealed that the lack of poor ideological base of political parties in Nigeria, selfish interests of members, inherent constitutional controversies, etc, constitute the major factors that heighten instability in internal democratic practice and hence, trigger the unbridled upsurge in inter-party defections. The study concluded by emphasizing that the problem would remain unabated unless there are among other things, a change in criteria for the selection of leaders of political parties and a constitutional amendment with regards to inter-party defections.